Conditions for the existence of bounded solutions of one class of nonlinear differential equations - Hrod, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For systems of nonlinear differential equations (dx/dt) = A(x)x + f(t) in a Banach space, we establish sufficient conditions for the existence of their solutions bounded on the entire real axis R.